Advances in Databases and Information Systems : 19th East European Conference, ADBIS 2015, Poitiers, France, September 8-11, 2015, Proceedings - Tadeusz, Morzy; Valduriez, Patrick; Bellatreche, Ladjel; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book constitutes the thoroughly refereed proceedings of the 19th East European Conference on Advances in Databases and Information Systems, ADBIS 2015, held in Poitiers, France, in September 2015. The 31 full papers and 18 short papers presented were carefully selected and reviewed from 135 submissions. The papers are organized in topical sections such as database theory and access methods; user requirements and database evolution; multidimensional modeling and OLAP; ETL; transformation, extraction and archiving; modeling and ontologies; time series processing; performance and tuning; advanced query processing; approximation and skyline; confidentiality and trust.
Database theory and access methods -- User requirements and database evolution -- Multidimensional modeling and OLAP -- ETL -- Transformation, extraction and archiving -- Modeling and ontologies -- Time series processing -- Performance and tuning -- Advanced query processing -- Approximation and skyline -- Cnfidentiality and trust.
Keywords: Database management; Data mining; Database Management; Information Systems Applications (incl. Internet).; Data Mining and Knowledge Discovery